2008
DOI: 10.1038/sj.bjp.0707408
|View full text |Cite
|
Sign up to set email alerts
|

Potential to inhibit growth of atherosclerotic plaque development through modulation of macrophage neopterin/7,8‐dihydroneopterin synthesis

Abstract: The rise in plasma neopterin observed with increasing severity of vascular disease is a strong indicator of the inflammatory nature of atherosclerosis. Plasma neopterin originates as the oxidation product of 7,8-dihydroneopterin secreted by g-interferon stimulated macrophages within atherosclerotic plaques. Neopterin is increasingly being used as a marker of inflammation during clinical management of patients with a range of disorders including atherosclerosis. Yet the role of 7,8-dihydroneopterin/neopterin sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 105 publications
(120 reference statements)
1
35
0
Order By: Relevance
“…In most respects, the pig BMDM studied in this work resembled human monocyte-derived macrophages more closely than mouse BMDM. All three species induce the enzyme GCH1, which generates the cofactor tetrahydrobiopterin (BH4), and the by-product neopterin, which is a common marker of inflammation (64). Like human macrophages, and in keeping with earlier findings on other pig macrophage populations, pig BMDM did not produce NO, nor did they induce arginine-metabolizing genes or CAT2 in response to LPS (44,45).…”
Section: Discussionsupporting
confidence: 49%
“…In most respects, the pig BMDM studied in this work resembled human monocyte-derived macrophages more closely than mouse BMDM. All three species induce the enzyme GCH1, which generates the cofactor tetrahydrobiopterin (BH4), and the by-product neopterin, which is a common marker of inflammation (64). Like human macrophages, and in keeping with earlier findings on other pig macrophage populations, pig BMDM did not produce NO, nor did they induce arginine-metabolizing genes or CAT2 in response to LPS (44,45).…”
Section: Discussionsupporting
confidence: 49%
“…However, many plaques displayed a combination of these characteristics over their length. Figure 2E), while plaque 27 had extremely high levels in four distinct sections [3][4][5][6], which were separated by regions of low levels (Figure 2A). The highest total neopterin level measured in the study was 18 nmol/g of plaque tissue and was found in a small bifurcation region labelled Section 3 of plaque 27 ( Figures 1A3 and 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous analysis of atherosclerotic plaques removed from carotid arteries showed neopterin concentrations ranging from 0.72 to 2.34 μmol/L within the whole plaque [15]. Within one individual plaque that we sectioned, we reported large variations in neopterin concentration ranging from 0.4 to 2.2 nmol/g of wet tissue [6]. Based on these limited data, there appears to be a large range of neopterin concentrations both between plaques and within an individual plaque.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations